Molluscicidal Activity of Some Solanum Species Extracts against the Snail Biomphalaria alexandrina - Gehad T. El-Sherbini; Rawia A. Zayed; Eman T. El-Sherbini (Journal of Parasitology Research)
Background. Snails' species are associated with transmission parasitic disease as intermediate host. Biological control stands to be a better alternative to the chemical controls aimed against snails. The search of herbal preparations that do not produce any adverse effects in the non-target organisms and are easily biodegradable remains a top research issue for scientists associated with alternative molluscicides control. Method. Solvent extracts of fresh mature leaves of S. nigrum, S. villosum, and S. sinaicum were tested against Biomphalaria alexandrina, a common intermediate host of schistosoma mansoni. A phytochemical analysis of chloroform: ethanol extract was performed to search for active toxic ingredient. The lethal concentration was determined. Results. Extracts isolated from mature leaves of Solanum species were found to be having molluscicidal properties. S. nigrum extract was recorded as the highest mortality rate. When the mortality of different solvent extracts was compared, the maximum (𝑃<.05) mortality was recorded at a concentration of 90 ppm of ethanol extract of S. nigrum. Conclusion. Extract of mature leaves of S. nigrum exhibited molluscicidal activity followed by S. sinaicum and the less one was S. villosum. The study provides considerable scope in exploiting local indigenous resources for snails' molluscicidal agents.